The Theological Significance of Pentecost: A Hermeneutical and Dogmatic Approach within the Eastern Orthodox Tradition - Andrew Lucas Tjong; Yohanes Bambang Cahyo Wicaksono (Journal Of Spirituality And Practical Theology, 2025)
This study examines the theological significance of Pentecost through a hermeneutical and dogmatic approach within the Eastern Orthodox tradition. Methodologically, it integrates a hermeneutical reading of Acts 2:1–13 with a doctrinal and liturgical-spiritual analysis rooted in the dogmatic theology and liturgical heritage of the Eastern Orthodox Church. The findings reveal that Pentecost is not merely a historical event, but a mystical and sacramental reality continuously experienced in the liturgical life of the Church. The descent of the Holy Spirit is interpreted as the fulfillment of Old Testament prophecy, the transformation of the apostolic community, a universal missionary mandate, and the realization of mysterion (divine mystery) through the sacraments and worship. Thus, Pentecost becomes a convergence of Scripture, doctrine, and liturgy, offering a dynamic and Christocentric vision of the Spirit-filled life in the Church.